Banks, credit market frictions, and business cycles - Ali Dib (Bank of Canada, 2010)
The author proposes a micro-founded framework that incorporates an active banking sector into a dynamic stochastic general-equilibrium model with a financial accelerator. He evaluates the role of the banking sector in the transmission and propagation of the real effects of aggregate shocks, and assesses the importance of financial shocks in U.S. business cycle fluctuations. The banking sector consists of two types of profitmaximizing banks that offer different banking services and transact in an interbank market. Loans are produced using interbank borrowing and bank capital subject to a regulatory capital requirement. Banks have monopoly power, set nominal deposit and prime lending rates, choose their leverage ratio and their portfolio composition, and can endogenously default on a fraction of their interbank borrowing. Because it is costly to raise capital to satisfy the regulatory capital requirement, the banking sector attenuates the real effects of financial shocks, reduces macroeconomic volatilities, and helps stabilize the economy. The model also includes two unconventional monetary policies (quantitative and qualitative easing) that reduce the negative impacts of financial crises.
Keywords: E32; E44; G1; 330; Economic models; Business fluctuations and cycles; Credit and credit aggregates; Financial stability; Wirtschaftskrise; Schock; Bankgeschäft; Transmissionsmechanismus; Akzelerator; Konjunktur; USA